Modulation of Cellular Protein Trafficking by Human Immunodeficiency Virus Type 1 Nef: Role of the Acidic Residue in the ExxxLL Motif - Coleman, Scott H. (American Society for Microbiology, 2006)
The nef gene contributes to the replication of primate lentiviruses by altering the trafficking of cellular proteins involved in adaptive immunity (class I and II major histocompatibility complex [MHC]) and viral transmission (CD4 and DC-SIGN). A conserved acidic leucine-based sequence (E(160)xxxLL) within human immunodeficiency virus type 1 (HIV-1) Nef binds to the cellular adaptor protein (AP) complexes, which mediate protein sorting into endosomal vesicles. The leucine residues in this motif are required for the down-regulation of CD4 and for the up-regulation of DC-SIGN and the invariant chain of MHC class II, but the role of the acidic residue is unclear. Here, substitution of E160 with uncharged residues impaired the ability of Nef to up-regulate the expression of the invariant chain and DC-SIGN at the cell surface, whereas substitution with a basic residue was required for a similar effect on the down-regulation of CD4. All substitutions of E160 relieved the Nef-mediated block to transferrin uptake. E160 was required for the efficient interaction of Nef with AP-1 and AP-3 and for the stabilization of these complexes on endosomal membranes in living cells. Systematic mutation of the ExxxLL sequence together with correlation of binding and functional data leads to the hypotheses that AP-1 and AP-3 are major cofactors for the effect of Nef on the trafficking of transferrin, are less important but contribute to the modulation of the invariant chain and DC-SIGN, and are least critical for the modulation of CD4. The data suggest that the E160 residue plays a differential role in the modulation of leucine-dependent Nef-targets and support a model in which distinct AP complexes are used by Nef to modulate different cellular proteins.